Evaluation of geriatric assessment and management on the toxic effects of cancer treatment (GAP70+): a cluster-randomised study. Issue 10314 (20th November 2021) - Mohile, Supriya G; Mohamed, Mostafa R; Xu, Huiwen; Culakova, Eva; Loh, Kah Poh; Magnuson, Allison; Flannery, Marie A; Obrecht, Spencer; Gilmore, Nikesha; Ramsdale, Erika; Dunne, Richard F; Wildes, Tanya; et al.
Summary: Background: Older adults with advanced cancer are at a high risk for treatment toxic effects. Geriatric assessment evaluates ageing-related domains and guides management. We examined whether a geriatric assessment intervention can reduce serious toxic effects in older patients with advanced cancer who are receiving high risk treatment (eg, chemotherapy). Methods: In this cluster-randomised trial, we enrolled patients aged 70 years and older with incurable solid tumours or lymphoma and at least one impaired geriatric assessment domain who were starting a new treatment regimen. 40 community oncology practice clusters across the USA were randomly assigned (1:1) to the intervention (oncologists received a tailored geriatric assessment summary and management recommendations) or usual care (no geriatric assessment summary or management recommendations were provided to oncologists) by means of a computer-generated randomisation table. The primary outcome was the proportion of patients who had any grade 3–5 toxic effect (based on National Cancer Institute Common Terminology Criteria for Adverse Events version 4) over 3 months. Practice staff prospectively captured toxic effects. Masked oncology clinicians reviewed medical records to verify. The study was registered with ClinicalTrials.gov, NCT02054741 . Findings: Between July 29, 2014, and March 13, 2019, we enrolled 718 patients. Patients had a mean age of 77·2 years (SD 5·4) and 311 (43%) of 718 participants were female. The mean number of geriatric assessment domain impairments was 4·5 (SD 1·6) and was not significantly different between the study groups. More patients in intervention group compared with the usual care group were Black versus other races (40 [11%] of 349 patients vs 12 [3%] of 369 patients; p<0·0001) and had previous chemotherapy (104 [30%] of 349 patients vs 81 [22%] of 369 patients; p=0·016). A lower proportion of patients in the intervention group had grade 3–5 toxic effects (177 [51%] of 349 patients) compared with the usual care group (263 [71%] of 369 patients; relative risk [RR] 0·74 (95% CI 0·64–0·86; p=0·0001). Patients in the intervention group had fewer falls over 3 months (35 [12%] of 298 patients vs 68 [21%] of 329 patients; adjusted RR 0·58, 95% CI 0·40–0·84; p=0·0035) and had more medications discontinued (mean adjusted difference 0·14, 95% CI 0·03–0·25; p=0·015). Interpretation: A geriatric assessment intervention for older patients with advanced cancer reduced serious toxic effects from cancer treatment. Geriatric assessment with management should be integrated into the clinical care of older patients with advanced cancer and ageing-related conditions. Funding: National Cancer Institute